Abuse of power is a defect of will in English law A comparative study of Iraqi law - علي, يونس صلاح الدين (Journal of Legal Sciences, 2018)
Undue influence is considered as a vitiating factor or defect in English law. It is a dominating influence, with which the ascending party enjoys, and which enables him to exert an illegitimate pressure on the unduly influenced weaker party, in order to induce, or force him, to conclude a contract and enter into a transaction, against his will. It is also worth-bearing in mind that the doctrine of undue influence is an equitable one, originating from the rules of equity, applied by English courts of equity, and by which these courts set aside unconscionable bargains, in which one party is in a position to exploit the weakness of the other.  It is also worth-mentioning that this doctrine has been included in the English common law. Whereas the Iraqi Civil Law No. 40 of 1951 has enacted and organized the ascendency or the moral influence.